Effects of tramadol on respiration and basal metabolism - Castañeda, Benjamin (2022)
We have studied the action of Tramadol (a potent anagesic) over the respiratory center and the metabolism in rats. We used the minute respiratory volume and the metabolic rate as parameters of our study. We found that variations in both parameters had close relationship. The minute respiratory volume and the metabolic rate got a significant increase by the action of Tramadol.